Nutrient response and yield of mungbean in response to zinc and iron through agronomic mechanism of biofortification - B.C. Dhayal; U.N. Shukla; Ummed Singh; Sita Ram Kumhar; Ramdev Sutaliya (Annals of Agricultural Research, 2025)
A field experiment was conducted at College of Agriculture, Agriculture University, Jodhpur in kharif season during 2020 and 2021 to study the effect of agronomic biofortification of zinc and iron on yield and nutrient response of mungbean [Vigna radiata (L.) Wilczek] varieties. The experiment was laid out in a split plot design, comprised with two varieties namely GM-7 and MH-421 and three treatments of foliar spray of iron (Fe) and urea in main-plots and four treatments included seed inoculation by zinc solubilizing bacteria with soil application of zinc (Zn) in a combinations were assigned to sub-plots. In this way, the experiment had twenty four treatment combinations were replicated thrice. Mung bean variety ‘MH-421’ had performed prominently with respect to yield and nutrient response. Biofortified treatment of iron with urea spray and zinc significantly higher seed yield, ABR, iron and zinc response were recorded under treatment foliar spray of 0.5% Fe + 2% urea at flower initiation and pod formation stages and seed inoculation with ZSB + soil application of higher dose of zinc sulphate i.e. ZSB (SI) + 25 kg ZnSO4/ha, which remained at par with foliar spray of 0.5% Fe + 2% urea at flower initiation stage and ZSB (SI) + 20 kg ZnSO4/ha at 25, 50 DAS and at harvest stage of mungbean, respectively.